2019
DOI: 10.1002/lt.25608
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Gene Programs in the Blood During Liver Regeneration in Living Liver Donors

Abstract: The human liver’s capacity to rapidly regenerate to a full‐sized functional organ after resection has allowed successful outcomes for living donor liver transplantation (LDLT) procedures. However, the ability to detect and track physiological changes occurring during liver regeneration after resection and throughout the restoration process is still lacking. We performed a comprehensive whole‐transcriptome RNA sequencing analysis of liver and circulating blood tissue from 12 healthy LDLT donors to define biomar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 37 publications
4
15
0
Order By: Relevance
“…We have shown that pharmacological activation of Nrf2 in primary human hepatocytes results in the modulation of genes that are associated with enhanced liver regeneration in Accepted Article mice treated with CDDO-Me. In addition, it has recently been reported that many of these processes are also modulated in the remnant liver within four hours of surgery in patients (34,35). These findings highlight the potential translational importance of our work.…”
Section: Discussionsupporting
confidence: 63%
“…We have shown that pharmacological activation of Nrf2 in primary human hepatocytes results in the modulation of genes that are associated with enhanced liver regeneration in Accepted Article mice treated with CDDO-Me. In addition, it has recently been reported that many of these processes are also modulated in the remnant liver within four hours of surgery in patients (34,35). These findings highlight the potential translational importance of our work.…”
Section: Discussionsupporting
confidence: 63%
“…The network analysis approach used on liver regeneration showed complex interactions between the Hippo signaling pathways with others signaling pathways including TNF-a, IL-6, IFN-γ (interferon-gamma), Hedgehog, Notch, TGF-β, and WNT. [192][193][194][195] TNF-α, IL-6, and IFN-γ signaling pathways display crucial roles in the induction of innate immune responses during the acute peak of liver regeneration, happening between 2 and 120 minutes after PHx, in donors and recipients of liver transplant. During this phase, different components of the innate immune system are recruited and activated into the injured liver, including macrophages, neutrophils, and mast cells, promoting activation of liver regeneration through IL-6 cytokine production.…”
Section: Modulation By Cytokines Growth Factors and Metabolic Signaling Pathways At Different Stages Of Liver Regenerationmentioning
confidence: 99%
“…During this phase, different components of the innate immune system are recruited and activated into the injured liver, including macrophages, neutrophils, and mast cells, promoting activation of liver regeneration through IL-6 cytokine production. 194 Inactivation of the Hippo signaling leads to recruitment of YAP/TAZ into the nucleus and form a complex with SMADS and β-Catenin, respectively, key components of the TGF-β and WNT signaling pathways, promoting the transcription of target genes that govern overall cell proliferation and tissue growth. 192 Upon liver injury, HSCs are activated and upregulate the expression of Jag1, the Notch ligand, through YAP, promoting Notch signaling and biliary specification in oval cells/hepatic pluripotent cells.…”
Section: Modulation By Cytokines Growth Factors and Metabolic Signaling Pathways At Different Stages Of Liver Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…The evolving technique of next-generation sequencing opened new doors for a deeper understanding of pathophysiological processes of liver regeneration, diseases and in the field of liver transplantation (Nicastro and D'Antiga 2018;Chen et al 2018;Lawrence et al 2019;Yang et al 2020). Indeed, the field of machine perfusion of liver allografts lacks the application of these new up-to-date techniques, which will yield to gain insights into the molecular principles that underlie the protective effects of allograft machine perfusion before liver transplantation.…”
Section: Introductionmentioning
confidence: 99%